Direct Oral anticoagulants in pulmonary thromboembolism therapy: the generalization-individualization dilemma and the path to risk stratification—a perspective - Meng, Cheng; Wang, Hao (Frontiers in Medicine, 2025)
Direct oral anticoagulants (DOACs) have transformed the management of pulmonary thromboembolism (PTE), supported by robust evidence from phase III clinical trials and subsequent incorporation into international treatment guidelines. However, their fixed-dose convenience and simplified administration have also encouraged a trend toward generalized use in real-world practice, often overlooking essential individual factors such as comorbidities, dynamic physiological parameters, and specific clinical contexts. This perspective synthesizes current evidence and clinical insights from a narrative review of recent literature on the use of DOACs in PTE. It examines the factors promoting their broad application, identifies patient-specific risk profiles, and proposes a framework for dynamic risk stratification to guide personalized treatment. Future efforts should focus on developing and validating integrated stratification systems that incorporate clinical phenotypes, biomarker trends, and patient preferences. Such tools are essential to achieving truly personalized anticoagulation therapy, ultimately maximizing safety and efficacy for each individual with PTE.